2020
DOI: 10.1038/s41591-020-0949-6
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence of immunoglobulin M and G antibodies against SARS-CoV-2 in China

Abstract: Detection of asymptomatic or subclinical novel human coronavirus SARS-CoV-2 infection is critical for understanding the overall prevalence and infection potential of COVID-19. To estimate the cumulative prevalence of SARS-CoV-2 infection in China, we evaluated the host serologic response, measured by the levels of immunoglobulins M and G in 17,368 individuals, in the city of Wuhan, the epicenter of the COVID-19 pandemic in China, and geographic regions in the country, during the period from 9 March 2020 to 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
397
9
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(462 citation statements)
references
References 10 publications
44
397
9
12
Order By: Relevance
“…In this study, the age of COVID-19/PLWHA was older than the other PLWHA, which was consistent with that in the overall COVID-19 population, i.e., the older males had a higher proportion in the COVID-19 patients [2]. Furthermore, our study suggested that older age was a risk factor for HIV/AIDS suffered COVID-19, which was also similar to the HIV negative population [19].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, the age of COVID-19/PLWHA was older than the other PLWHA, which was consistent with that in the overall COVID-19 population, i.e., the older males had a higher proportion in the COVID-19 patients [2]. Furthermore, our study suggested that older age was a risk factor for HIV/AIDS suffered COVID-19, which was also similar to the HIV negative population [19].…”
Section: Discussionsupporting
confidence: 86%
“…The multivariable results also indicated that the log transferred CD4 count was negatively associated with the occurrence of COVID-19 (AOR=0.06, 95%: CI 0.01-0.30), while log transferred length from HIV diagnosis was positively associated with the occurrence of COVID-19 (AOR=1.12, 95% CI:1.05-1. 19).…”
Section: Factors Associate With Covid-19 Among Plwhamentioning
confidence: 99%
See 1 more Smart Citation
“…This is not on par with the dynamic regularity of antibodies in other viral infection. Many similar results have reported that the serum antibodies dynamic of this novel virus surprised all of us 17,[21][22][23] .We also found that without breast feeding, the maternal protective effect in infants was rapidly eliminated naturally within two months after birth ( Table 3). It is worth noting that this rate of decline was beyond expectations.…”
Section: Resultssupporting
confidence: 75%
“…High specificity is critical to avoid misinterpretations or false positives, unnecessary stress and quarantine, and to prevent controversies and wrong conclusions for surveillance or prevalence studies [23][24][25][26][27][28][29] . On the other hand, currently no antibody avidity test 7,[30][31][32][33][34] exists for COVID-19 to assess the antibody maturation and infer the timing of recent as opposed to remote infection.…”
mentioning
confidence: 99%